Development and evaluation of three-dimensional transfers to depict skin conditions in simulation-based education - Schnabel, Kai Philipp; Lörwald, Andrea Carolin; Beltraminelli, Helmut; Germano, Miria; Brem, Beate Gabriele; Wüst, Sandra; Bauer, Daniel (GMS Journal for Medical Education, 2024)
Modern medical moulages are becoming increasingly important in simulation-based health professions education. Their lifelikeness is important so that simulation engagement is not disrupted while their standardization is crucial in high-stakes exams. This report describes in detail how three-dimensional transfers are developed and produced so that educators will be able to develop their own. In addition, evaluation findings and lessons learnt from deploying transfers in summative assessments are shared.Step-by-step instructions are given for the creation and application of transfers, including materials and photographic visualizations. We also examined feedback on 10 exam stations (out of a total of 81) with self-developed three-dimensional transfers and complement this with additional lessons learnt. By the time of submission, the authors successfully developed and deployed over 40 different three-dimensional transfers representing different clinical findings in high-stakes exams using the techniques explained in this article or variations thereof. Feedback from students and examiners after completing the OSCE is predominantly positive, with lifelikeness being the quality most often commented upon. Caveats derived from feedback and own experiences are included.The step-by-step approach reported can be adapted and replicated by healthcare educators to build their own three-dimensional transfers. This should widen the scope and the lifelikeness of their simulations. At the same time we propose that this level of lifelikeness should be expected by learners as not to disrupt simulation engagement. Our evaluation of their use in high-stakes assessments suggests they are both useful and accepted.